A adolescência e o des-prazer do saber escolar - Silva, Dejanira Lieta Corrêa e (2012)
Through social and bibliographic research the present paper has dedicated itself to bring a more up to date vision of how young adults/teenagers/students of the first year of high school, belonging both to public and private schools of Paracatu-MG, perceive school and their teachers in regard to their desire to learn, the quality of their classes and the relationships they establish. The relevance of this investigation consists on the fact that knowing how teenagers read and contextualize the school environment through their necessities. It s known that several factors influence and are present on the youthful universe and, among them, it is school. It is considered as a sociocultural space where a multitude of ideas and behaviors express themselves in many different ways. This research has structured itself in 2 main parts that complement themselves. On the first part, there is a dialogue of the concept of adolescence and youth, their characteristics and relations. This is supported by: Alícia Fernandes, Arminda Aberastury, Contardo Calligaris, Daniel Becker, Erick Erikson, Guilhermo Carvajal, Guy Debord, José Gimeno Sacristán, José Outeiral, Luiz Antônio Groppo, Márcio Marguella, Marília Pontes Sposito, Mario Alighiero Manacorda, Maurício Knobel, Paulo Freire, Philippe Áries, Roberto Daunis, Sara Paín, among many others who have helped understand the academic context and the adolescence process. On the legal aspect, I make use of the Federal Constitution of 1988, the Constitutional Amendment nº 65 and the Child and Adolescent Statute. On the second part, it s established a dialogue between the theorical contribution, my experience as an educator and the results obtained through my researches. This way, I have worked on finding my research question, once teenagers speech show that the school universe and the youth contextualization need reframes.